Complete hyperentangled-Bell-state analysis for photonic qubits assisted by a three-level Λ-type system - Wang, Tie-Jun (Sci Rep, 2016)
Hyperentangled Bell-state analysis (HBSA) is an essential method in high-capacity quantum communication and quantum information processing. Here by replacing the two-qubit controlled-phase gate with the two-qubit SWAP gate, we propose a scheme to distinguish the 16 hyperentangled Bell states completely in both the polarization and the spatial-mode degrees of freedom (DOFs) of two-photon systems. The proposed scheme reduces the use of two-qubit interaction which is fragile and cumbersome, and only one auxiliary particle is required. Meanwhile, it reduces the requirement for initializing the auxiliary particle which works as a temporary quantum memory, and does not have to be actively controlled or measured. Moreover, the state of the auxiliary particle remains unchanged after the HBSA operation, and within the coherence time, the auxiliary particle can be repeatedly used in the next HBSA operation. Therefore, the engineering complexity of our HBSA operation is greatly simplified. Finally, we discuss the feasibility of our scheme with current technologies.